Studi Pemodelan Daya Dukung Fondasi Telapak Pada Tanah Lempung Dengan Perkuatan Geotekstil Woven - Putra, Hendri Gusti; Andriani, Andriani; Hakam, Abdul; Boyosa, Viola De (Universitas Andalas, 2023)
One of the important things in developing decent residential land is the availability of buildings, facilities and infrastructure that are safe and comfortable to live in. However, with the development of settlements and increasingly expensive land, the use of areas with soft soil conditions cannot be avoided. Construction on soft soil causes many problems, including the relatively low bearing capacity of the soil and large settlements so that soil stability is disturbed. The low shear strength of clay soil causes the shear stress generated by the foundation to be large enough to cause the construction building to collapse. To overcome these soil conditions, the soft clay soil is stabilized first. One way to overcome this problem is to add reinforcement material, namely geotextiles. Geotextiles can develop very high tensile strength. Apart from that, geotextiles also function as a filter and hold fine particles so that they are not carried away by water seepage, separating two layers between soil and soil or soil and water so that they do not mix with each other. In this research, modeling will be carried out with variations in the number of geotextile layers, namely 1 layer with a depth of 5 cm, 1 layer with a depth of 10 cm, and 2 layers with a depth of 5 & 10 cm, which will be compared with without using geotextiles. The results of the research showed that the soil bearing capacity in the laboratory with 2 layers of woven geotextile reinforcement with a depth of 5 & 10 cm had the highest value of 9.723N/cm2. As well as the soil bearing capacity in the plaxis software, the highest bearing capacity was found in the hardening soil model material with a depth of 5 cm, amounting to 46,402 N/cm2.​